Primary focal segmental glomerulosclerosis in second trimester pregnancy presenting as rapidly progressive renal failure: diagnostic and therapeutic challenges: a case report - Adane Petros; Addisu Melkie; Yidnekachew Asrat; Fitsum A. Gemechu; Yewondwossen Tadesse (Journal of Medical Case Reports)
Abstract Background Proteinuria in pregnancy is often attributed to preeclampsia, but primary glomerular diseases such as focal segmental glomerulosclerosis can also present during pregnancy, complicating diagnosis and management. Case presentation A 29-year-old gravida 2, para 1 African woman presented at 25 weeks of gestation with generalized edema and turbid urine. Initial investigations revealed nephrotic-range proteinuria (7.2 g/24 hours), hematuria with red blood cell casts, and deteriorating renal function, with serum creatinine rising from 1.8 to 5 mg/dL within 3 days. Due to worsening renal impairment, pregnancy termination was performed, leading to partial renal recovery, though nephrotic-range proteinuria persisted. Renal biopsy at 4 months postpartum confirmed primary focal segmental glomerulosclerosis. Conclusions Early recognition and prompt treatment of pregnancy-associated glomerular disease are vital for renal recovery. Differentiating focal segmental glomerulosclerosis from preeclampsia is essential, and targeted immunosuppressive therapy can achieve sustained remission, highlighting the need for a multidisciplinary approach.